PENERAPAN GAME DALAM BAHAN AJAR BAHASA INDONESIA SMP - Asih Andriyati Mardliyah (CARAKA, 2018)
This study aims to produce Indonesian language teaching materials that attract the learning interest of Junior High School through the application of games, and obtain the meaningfulness of game-based teaching materials for improving student learning achievement in learning Indonesian. This study uses research and development methods. The method stage includes: (1) the preliminary study phase, including literature study, observation and interviews; (2) the stage of developing teaching material models by applying games; and (3) evaluation stage to test the effectiveness of teaching materials. The results of the study concluded that; there were differences in achievement between the control group (using old teaching materials) and the experimental group (using game-based Indonesian language teaching materials). By using technical analysis of independent sample t-test, the significance of 0,000 or less is obtained from the 0.05 significance level. In other words, game-based Indonesian language teaching materials are better than old teaching materials.